Struktur Histologi Usus Ikan Asang (Osteochilus hasseltii C.V.) yang Terdapat di Danau Singkarak, Sumatera Barat - Sulastri, Sulastri; Zakaria, Indra Junaidi; Marusin, Netty (Metamorfosa: Journal of Biological Sciences; Vol 5 No 2 (2018)DO - 10.24843/metamorfosa.2018.v05.i02.p12, 2018)
A study about “intestine histology structure of Silver Sharkminnow ( Osteochilus hasseltii C.V) in Singkarak Lake, West Sumatera” has been done at Animal Structure and Developmental Laboratory, Department of Biology, Mathematic and Science Faculty, Andalas University, Padang. This study used an observational method to microscopically examine the histology of intestinal asang fish (Osteochilus hasseltii C.V.) directly at four locations in Lake Singkarak, namely Sumani, Paninggahan, Sumpur, Ombilin using purposive sampling method.. Histolgical samples of intestine were isolated, fixated, dehydrated and embedded on paraffin, stained using Haematoxylin-Eosin and observation using microscope. The results showed some histological alteration of gastrc and intestine samples in each location. Those alteration varied from edema , vili erotion, hemorrhage, lysis and necrosis.